2008
DOI: 10.1093/ajcn/88.2.529s
|View full text |Cite
|
Sign up to set email alerts
|

25-Hydroxyvitamin D: functional outcomes in infants and young children

Abstract: Vitamin D deficiency occurs in the United States in exclusively breastfed infants who have high levels of skin pigmentation, inadequate vitamin D supplementation, and insufficient sunlight exposure. I review serum 25-hydroxyvitamin D [25(OH)D] concentrations and functional outcomes of vitamin deficiency in young children and breastfed and nonbreastfed infants. These outcomes include the presence or absence of vitamin D deficiency rickets, bone mineral content, and serum parathyroid hormone concentration. Daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
85
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(94 citation statements)
references
References 38 publications
5
85
0
4
Order By: Relevance
“…Selection bias may likely explain the high frequency of vitamin D supplementation. Despite the high frequency of supplementation, a longer period of exclusive breastfeeding and breastfeeding at 9 months were both significantly associated with lower levels of 25(OH)D. We found that the dietary intake of vitamin D was positively associated with 25(OH)D. The intake did also include infant formula and enriched commercial baby foods, whereas it did not include the content of vitamin D in breast milk, which is, on the other hand, known to be low (Greer, 2008). In all, 92% of the infants who were not breastfed at 9 months received infant formula, indicating that breast milk replaces an energy intake from more vitamin D-rich sources.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Selection bias may likely explain the high frequency of vitamin D supplementation. Despite the high frequency of supplementation, a longer period of exclusive breastfeeding and breastfeeding at 9 months were both significantly associated with lower levels of 25(OH)D. We found that the dietary intake of vitamin D was positively associated with 25(OH)D. The intake did also include infant formula and enriched commercial baby foods, whereas it did not include the content of vitamin D in breast milk, which is, on the other hand, known to be low (Greer, 2008). In all, 92% of the infants who were not breastfed at 9 months received infant formula, indicating that breast milk replaces an energy intake from more vitamin D-rich sources.…”
Section: Discussionmentioning
confidence: 73%
“…What defines an optimal concentration of 25(OH)D in children is an important question, but consensus has not been reached (Vieth, 2006;Wagner and Greer, 2008). Breastfeeding without vitamin D supplementation is a predictor of vitamin D deficiency (Gordon et al, 2008;Greer, 2008). Only 7 out of 255 infants did not receive vitamin D supplements during the first 9 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D is also synthesized when human skin is exposed to sunlight; dark skin synthesizes vitamin D at a slower rate 6 . Therefore, children in low income sub-Saharan Africa countries are perhaps paradoxically some of the most susceptible to rickets 7, 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Плацен-та играет огромную роль в превращении 25(OH)D в 1,25(OH) 2 D (который не способен проникать че-рез плаценту) за счет активности 1α-гидроксилазы, благодаря чему возможно увеличение содержания 1,25(OH) 2 D у матери и плода до 2 раз [8][9][10]. По-вышенная концентрация 1,25(OH) 2 D способствует снижению уровня провоспалительных цитокинов, предотвращает развитие преэклампсии и прежде-временные роды, участвует в регуляции секреции половых гормонов (эстрадиола и прогестерона) [11,12]. После родов отмечается значительное сни-жение уровня 25(OH)D и 1,25(OH) 2 D.…”
unclassified